A rare case of blood stream infection due to Candida ciferii in an immuno-compromised patient - Choudhari, Sonali; Kale, Swati; Pathak, Anand; Mishra, Pradeep; Deshpande, Girish (International Journal of Advances in Medicine, 2019)
Invasive infections related to yeast are increasingly observed in immune-compromised patients in hospitals.Fungal infections have increased morbidity and mortality and prolonged hospital stay which can lead to rise in medical care costs. Non-albicans Candida species have been increasingly found as causative agents in human infections with important therapeutic implications. We present a case of a 37-year-old, female patient, known case of B cell Acute Lymphoblastic Leukaemia admitted in a tertiary care hospital in central India for supportive care and chemotherapy. Patient was responding well to chemotherapy. On post induction day 20, she complained of high-grade fever with abdominal pain.Two sets of blood culture were sent to Microbiology Diagnostic Laboratory for diagnosis. She was started on Injection Magnex Forte (Cefoperazone-Sulbactum) empirically.The Gram stain of positive blood culture showed Gram positive budding yeast like cells in all four bottles.The organism was identified as C. ciferrii on Vitek 2 with 95% identification.Antibiotic susceptibility testing showed sensitive to Amphotericin B MIC ≤0.25 and voriconazole MIC ≤0.12. It was resistant to fluconazole MIC ≥64 μg/ml.